Comparison of Diagnostic Accuracy of Transvaginal with Transabdominal Ultrasound for Ectopic Pregnancy - Nisar, Maria; Khan, Muhammad Imran (Indus Journal of Bioscience Research, 2025)
Introduction: Ectopic pregnancy (EP) has remained a significant source of maternal morbidity and mortality over the years. Proper identification of this disease is crucial to avoid or lessen the effects. A recent imaging technique used to assess the parametria is transvaginal ultrasound, which is more accurate than transabdominal ultrasound. Objectives: To establish the performance of TVS and TAUS in diagnosing EP about laparotomy, the reference technique. Study Design and Settings: This cross-sectional study was conducted at the Department of Radiology in Lady Reading Hospital, Peshawar, Pakistan from 11th July, 2024 to 10th January, 2025. Materials and Methods: This was a cross-sectional study involving 279 women aged 15–45 with suspected EP. All participants underwent TVS, TAUS, and laparotomy for confirmation. Sensitivity, specificity, and PPV, as well as NPV, for both modalities were computed. Results: The TVS was found to have a better sensitivity of 93.8% as compared to an assay of 78.6% by TAUS, better specificity of 82.4% as compared to the assay of 64.9% by TAUS, better PPV of 95.1% as compared to the assay of 85.3% by TAUS and better accuracy of 91.4%. Conclusion: The study shows that TVS is more accurate than TAUS in diagnosing EP and its confirmatory role in imaging.